The impact of highways on population redistribution: The role of land development restrictions - Or Levkovich; Jan Rouwendal; Jos van Ommeren (Tinbergen Institute, 2017)
We study the role of land development restrictions for the effects of highway expansion on the spatial distribution of population. We demonstrate that these restrictions strongly interfered with the effects of highways in the Netherlands. Introducing an IV approach to address endogenous interaction variables, our findings show that new highways accelerated population growth in peripheral areas, but had no such effect in central cities and suburban municipalities. We find that due to development restrictions near larger cities, the highway expansion caused a `leapfrog' pattern, in which suburban growth skipped development-restricted areas and expanded into farther located peripheral areas.
Keywords: R11; R58; R52; 330; highways; development restrictions; population redistribution; suburbanization; instrumental variables; endogenous interaction variables